Effects of alkyl side chains and terminal hydrophilicity on vitamin D receptor (VDR) agonistic activity based on the diphenylpentane skeleton. Issue 22 (15th November 2015) - Misawa, Takashi; Yorioka, Momoko; Demizu, Yosuke; Noguchi-Yachide, Tomomi; Ohoka, Nobumichi; Kurashima-Kinoshita, Megumi; Motoyoshi, Hitomi; Nojiri, Hisao; Kittaka, Atsushi; Makishima, Makoto; Naito, Mikihiko; Kurihara, Masaaki
Graphical abstract: Abstract: Vitamin D receptor (VDR) is a family of nuclear receptors (NR) that regulates physiological effects such as the immune system, calcium homeostasis, and cell proliferation. We synthesized non-secosteroidal VDR ligands bearing a long alkyl chain based on the diphenylpentane skeleton. The VDR-mediated transcriptional activities of the synthesized compounds were evaluated using a reporter gene assay and HL-60 cell differentiation-inducing assay. We herein described the structure–activity relationship and effects of alkyl-chain length on VDR-mediated transcriptional activity.